Phytochemical Study of Majoon-e-Junthyana to Evaluate the Liver Protective Effects - Shahma, A.H.F; Nazeem, M.H.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
In Unani System of Medicine, Jigar (Liver) is considered as Aaza e Raeesa (Vital organ) which produces Hararat ghariziyya (Innate heat) and Akhlat (humours) through Istehala (Metabolism). Hararat Ghariziyya and Akhlat play an important role in maintenance of health and thus, any derangement of these will lead to diseases. Unani Medicine provides a number of Murakkab adviya (Polyherbal formulation) with various pharmacological actions which have protective effects on Jigar. Majoon-eJunthyana is one of the important Murakkab Dawa used to treat liver related disorders. Therefore, this study was carried out to evaluate the liver protective effect of Majoon-e-Junthyana and to provide scientific evidences for its efficacy by exploring the phytochemical constituents of its ingredients. Classical texts, review articles and scientific journals from PubMed, Google Scholar and other electronic tools mainly from the year 2015 to 2024 were explored. The recent research findings revealed that the ingredients of this Murakkab dawa produce hepatoprotective effects due to cumulative biological activities of anti-inflammatory, anti- viral, anti-oxidant, antifibrotic, anti-diabetogenic, anti-hyperlipidemic and cytotoxic activities possessed by their chemical constituents especially flavonoids, sesquiterpenoids, alkaloids, anthraquinone, glycosides and their derivatives. These findings are consistent with the therapeutic effects of the ingredients of Majoon-e-Junthyana which have been described as Muqawwie e Jigar (Liver tonic), Muhallil e Warm (anti-inflammatory), Muaddil (Alterative of Su e Mizaj e Jigar), Mudir e Bole (Diuretic) and Mufettih e Sudad (Deobstruent) in Unani classical texts. It is evident from this study that the phytochemical constituents of the ingredients of Majoon-e-Junthyana possess liver protective effect.
Keywords: hepatoprotective activity; phytochemical constituent; Majoon-eJunthyana; liver tonic